Genetic mapping and molecular marker development for white flesh color in tomato - Liu, Jie; Fang, Xiaoxue; Yu, Fangjie; Zhang, Chengfeng; Fan, Pengfei; Wang, Ningdong; Shao, Qiao; Gan, Ning; Lv, Xiaolong; Ouyang, Bo; Zhang, Mingfang; Wu, Xinsheng; et al. (Frontiers in Plant Science, 2024)
Fruit color significantly influences the quality of horticultural crops, which affects phytochemical diversity and consumer preferences. Despite its importance, the genetic basis of the white-colored fruit in tomatoes remains poorly understood. In this study, we demonstrate that white-fleshed tomato varieties accumulate fewer carotenoids than yellow-fleshed varieties. We developed various segregating populations by hybridizing red, yellow, and white fruit tomato cultivars. Genetic analysis revealed that the white fruit color trait is controlled by a single gene that dominates both red and yellow fruits. Bulk segregant RNA sequencing provided a preliminary map of a 3.17 Mb region on chromosome 3 associated with the white color trait. Based on kompetitive allele-specific PCR (KASP) markers, we narrowed the candidate gene region to 819 kb. Within this region, we identified a 4906bp sequence absence variation near Phytoene Synthase 1 (SlPSY1) specific to white-colored tomatoes. Genotyping of the progeny and natural populations using a single nucleotide polymorphism adjacent to this absence of variation confirmed its key role in white fruit formation. Collectively, our findings provide insights into white fruit trait formation in tomatoes, enabling tomato breeders to precisely introduce white fruit traits for commercial exploitation.